Arahan Penataan Parkir pada Badan Jalan Kawasan Komersial Koridor Slamet Riyadi Kota Samarinda: Parking On Body Street Commercial Area - Syapolly, Yunia Indawati; Nugroho, Rizky Arif; Hidayat, Arief; Pratama, Maryo Inri (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2023)
The Slamet Riyadi Street corridor is one of the roads in Samarinda City with trade and service activities. On Slamet Riyadi road itself has a density of vehicle activity on certain days and hours. The preparation of research aimed at analyzing the direction of parking arrangement on the corridor of Jalan Slamet Riyadi. From the results of the analysis that has been carried out, the largest parking volume for cars was in corridor 1 as many as 130 cars on Thursday and for motor vehicles in corridor 1 as many as 381 motorcycles on Sunday. The highest parking turnover rate and the lowest parking index with a value of more than >1 vehicle/SRP and it is known that corridors 2 and 3 have a value of more than >1. An analysis of parking users was also carried out which obtained the average parking user aged >50 years. An analysis was carried out for direction on aspects of comfort, availability, distance and safety and it was found that maintenance of street lights, markings, road signs and the provision of parking attendants was needed and increased the distance to exit and enter parking so as not to endanger fellow road users.